Rationale V. On the Divine Offices - William Durand (Brepols, 2015)
William Durand (c. 1230-Nov. 1, 1296), Bishop of Mende, France, was unquestionably the most renowned liturgical scholar of the later Middle Ages. His encyclopedic allegorical exposition of the rites and worship services of the Latin Church, the <span class=